Biochemical and toxinological characterization of Naja sumatrana (Equatorial spitting cobra) venom - Yap,MKK (2011)
The lethal and enzymatic activities of venom from Naja sumatrana (Equatorial spitting cobra) were determined and compared to venoms from three other Southeast Asian cobras (Naja sputatrix, Naja siamensis and Naja kaouthia). All four venoms exhibited the common characteristic enzymatic activities of Asiatic cobra venoms: low protease, phosphodiesterase, alkaline phosphomonoesterase and L-amino acid oxidase activities, moderately high acetylcholinesterase and hyaluronidase activities and high phospholipase A2. Fractionation of N. sumatrana venom by Resource® S cation exchange chromatography (GE Healthcare, USA) yielded nine major protein peaks, with all except the acidic protein peak being lethal to mice. Most of the protein peaks exhibit enzymatic activities, and L-amino acid oxidase, alkaline phosphomonoesterase, acetylcholinesterase, 5'-nucleotidase and hyaluronidase exist in multiple forms. Comparison of the Resource® S chromatograms of the four cobra venoms clearly indicates that the protein composition of N. sumatrana venom is distinct from venoms of the other two spitting cobras, N. sputatrix (Javan spitting cobra) and N. siamensis (Indochinese spitting cobra). The results support the revised systematics of the Asiatic cobra based on multivariate analysis of morphological characters. The three spitting cobra venoms exhibit two common features: the presence of basic, potentially pharmacologically active phospholipases A2 and a high content of polypeptide cardiotoxin, suggesting that the pathophysiological actions of the three spitting cobra venoms may be similar.